Interactions of photosynthesis with genome size and function - Raven, John A. (The Royal Society, 2013)
Photolithotrophs are divided between those that use water as their electron donor (Cyanobacteria and the photosynthetic eukaryotes) and those that use a different electron donor (the anoxygenic photolithotrophs, all of them Bacteria). Photolithotrophs with the most reduced genomes have more genes than do the corresponding chemoorganotrophs, and the fastest-growing photolithotrophs have significantly lower specific growth rates than the fastest-growing chemoorganotrophs. Slower growth results from diversion of resources into the photosynthetic apparatus, which accounts for about half of the cell protein. There are inherent dangers in (especially oxygenic) photosynthesis, including the formation of reactive oxygen species (ROS) and blue light sensitivity of the water spitting apparatus. The extent to which photolithotrophs incur greater DNA damage and repair, and faster protein turnover with increased rRNA requirement, needs further investigation. A related source of environmental damage is ultraviolet B (UVB) radiation (280–320 nm), whose flux at the Earth's surface decreased as oxygen (and ozone) increased in the atmosphere. This oxygenation led to the requirements of defence against ROS, and decreasing availability to organisms of combined (non-dinitrogen) nitrogen and ferrous iron, and (indirectly) phosphorus, in the oxygenated biosphere. Differential codon usage in the genome and, especially, the proteome can lead to economies in the use of potentially growth-limiting elements